INTEGRASI KECERDASAN BUATAN DAN KOLABORATIF KAPABILITAS DINAMIS: KERANGKA STRATEGIS UNTUK MENINGKATKAN KINERJA DAN KEBERLANJUTAN PERUSAHAAN - Daryono, Daryono (LP2M Universitas Bina Bangsa, 2025)
The aim of this research is to explore the influence of artificial intelligence (AI) competencies on the dynamic capabilities and Sustainability of companies in a competitive and digital business landscape. This research identifies three main factors that influence the development of AI competencies—proactive attitude, collaboration across business functions (business spanning), and technology infrastructure. Empirical analysis shows that the third factor plays a significant role in strengthening AI competencies, which in turn enhances a company's dynamic capabilities. Dynamic capabilities, which include the ability to adapt to environmental changes, are identified as a key element in ensuring a company's long-term desirability. This research also reveals that companies that have strong AI competencies can leverage technology to optimize data-based decision making, accelerate innovation, and increase operational efficiency. Additionally, dynamic capabilities powered by AI are proven to support digestion through more efficient resource management and reduced environmental impact. This research provides theoretical contributions by strengthening the literature on dynamic capabilities and artificial intelligence, as well as practical contributions through guidance for companies to integrate AI technologies in their business strategies. The lender's research results include top management support, synergy between departments, and investment in modern technology infrastructure as the foundation for maximizing the benefits of AI.